PSYCHOPATHOLOGY AND PSYCHOTHERAPY IN ISLAM - Amiruddin Amiruddin (State Islamic University North Sumatra, 2015)
Abstrak: Psikopatologi dan Psikoterapi dalam Islam.Psikopatologi adalah penyakit jiwa yang kerap diderita manusia. Banyak faktor penyebab penyakit ini. Di antaranya adalah kehidupan modern yang ditandai dengan pola hidup yang materialistik, hedonisme dan egoistik. Dalam Islam, psikopatologi yang bersifat ukhrawi dideskripsikan sebagai bentuk penyimpangan dari norma-norma atau nilai- nilai moral, spiritual dan agama. Ada tiga bagian psikopatologi.Pertama, yang berkaitan dengan akidah atau berkaitan dengan Tuhan (ilâhiyah), sepertisyirik,kufur,zindiq, dan lain-lain.Kedua, yang berkaitan dengan kemanusiaan (insâniyah), sepertihasud, ‘ujub, ghadab, su’ al-zhan, dan lain-lain. Ketiga, gabungan kedua di atas, seperti riya’ dan nifaq. Psikoterapi adalah proses untuk mengobati penyakit jiwa individu dari berbagai problem. Al-Quran sebagai dasar ajaran Islam memuat informasi mengenai psikoterapi bagi orang-orang yang sakit jiwa. Pendekatan agamis sangat diperlukan untuk melakukan terapi dan mengembalikan kesehatan jiwa. Di samping itu, pendekatan agamis dapat membawa penderita psikopatologis dekat dengan Allah SWT.Abstract: Psychopathology is mental illness that has often suffered by human being. There are several factors that causes this illness, some of which are modern life characterized by materialistic, hedonistic and egoistic lives. In Islam, psychopathology which is described as a form of deviation from norms or moral values, spiritual and religion. Psychopathology is divided into three parts, namely those associated with faith, humanity and psychopathology which is associated with combination of faith and human being.Meanwhile psychotherapy is an effort to cure mental and psychiatric disorders suffered by individuals. Psychotherapy is a solution to cure various problems of mental disorders. Al-Qur’an, as the principles of Islamic teachings, contain information about psychotherapy for those who suffer from mental disorders. Religious approach is completely needed for therapy and it helps the psychopath recover from his/her mental disorders.TheQur’an could be used as a treatment as well as a preventive step, so that all human being will not suffer from mental disorders, and religious approach can bring the psychopaths closer to God, theAlmighty.Kata Kunci: psikopatalogi, psikoterapi, Islam